C(sp3)–F, C(sp2)–F and C(sp3)–H bond activation at silicon(ii) centers. Issue 71 (21st August 2017) - Swamy, V. S. V. S. N.; Parvin, Nasrina; Vipin Raj, K.; Vanka, Kumar; Sen, Sakya S.
Abstract : Silylene, [PhC(NtBu)2 SiN(SiMe3 )2 ] (1 ) underwent C(sp 3 )–F, C(sp 2 )–F and C(sp 3 )–H bond activation with trifluoroacetophenone, octafluorotoluene, and acetophenone, respectively, under ambient conditions. Abstract : Silylene [PhC(N t Bu)2 SiN(SiMe3 )2 ] (1 ) cleaves the C(sp 3 )–H and C–F bonds of acetophenone and 1, 1, 1-trifluoroacetophenone, respectively, under mild conditions. The reaction is initiated via a nucleophilic attack from the oxygen to the silicon atom followed by C–F/H bond cleavage. The scope of C–F bond activation has further been extended with C6 F6 and C6 F5 CF3 .